Significance of Mechnikov’s scientific inheritance for development of medicine - Semenova L.S.; Nykolaeva E.V. (Medičnì Perspektivi)
Ilya Ilyich Mechnikov is an outstanding scientist, zoologist, anatomist, embryologist, microbiologist, parasitologist, pathologist, bacteriologist, physiologist, cytologist, and immunologist. He was a resourceful and skilful biologist-experimenter, the author of the phagocytic theory of immunity. In 1908 I.I. Mechnikov together with the apologist of the humoral concept of immunity Paul Ehrlich was awarded the Nobel Prize in physiology and medicine «for research in the theory of immunity». The paper tells about the life and research of this scientist, importance of his researches for modern medicine.